Polarization Effects in Semiconductors From Ab Initio Theory to Device Applications - Wood, Colin; Jena, Debdeep (Springer US : Imprint: Springer, 2008)
Polarization Effects in Semiconductors: From Ab Initio Theory to Device Applications presents the latest understanding of the solid state physics, electronic implications and practical applications of the unique spontaneous or pyro-electric polarization charge of wurtzite compound semiconductors, and associated piezo-electric effects in strained thin film heterostructures. These heterostructures are used in wide band gap semiconductor based sensors, in addition to various electronic and opto-electronic semiconductor devices. The book covers the ab initio theory of polarization in cubic and hexagonal semiconductors, growth of thin film GaN, GaN/AlGaN GaAlN/ AlGaInN, and other nitrides, and SiC heterostructures. It discusses the effects of spontaneous and piezoelectric polarization on band diagrams and electronic properties of abrupt and compositionally graded heterostructures, electronic characterization of polarization-induced charge distributions by scanning-probe spectroscopies, and gauge factors and strain effects. In addition, polarization in extended defects, piezo-electric strain/charge engineering, and application to device design and processing are covered. The effects of polarization on the fundamental electron transport properties, and on the basic optical transitions are described. The crucial role of polarization in devices such as high electron mobility transistors (HEMTs) and light-emitting diodes (LEDs) is covered. The chapters are authored by professors and researchers in the fields of physics, applied physics and electrical engineering, who worked for 5 years under the "Polarization Effects in Semiconductors" DOD funded Multi Disciplinary University Research Initiative. This book will be of interest to graduate students and researchers working in the field of wide-bandgap semiconductor physics and their device applications. It will also be useful for practicing engineers in the field of wide-bandgap semiconductor device research and development.